Antusiasme Mahasiswa Universitas Nahdlatul Ulama Sidoarjo dalam Aktualisasi Kegiatan Keagamaan di Desa Sumokali - Zulfiah, Farah; Inayatullatifah; Lily Oktavia; Firda Amalia; M. Asfiyak H; Akyas Daksani A; Venny Fatmawati (LPPM, STAI Al-Azhar Menganti, 2022)
The Real Work Lecture activity is the role of students in implementing the Tri Dharma of Higher Education in the form of community service. The Real Work Lecture of the Nahdlatul Ulama University Sidoarjo in 2022 for groups of eight was held in Sumokali Village, Candi District, Sidoarjo Regency. In this article, the author takes an educational work program related to religion in Sumokali Village. Religious knowledge must be fostered from a young age, therefore activities in the religious field are carried out and will always exist in the lives of local communities in a region. This study uses qualitative methods and use observation techniques and data collection by documenting activities that have been carried out for more than one month. The following are the results of several religious activities that were participated in by group 8 students and students in Sumokali Village, namely routine Diba'an Activities, Al-Quran Khataman, Book Recitation with Ms. Muslimat, and Sunday Wage Recitation after the morning prayer congregation. These programs can be implemented well because students are able to establish good relationships with local Sumokali residents and empower themselves and are alert in participating in various religious activities in Sumokali Village. Keywords: Real Work Lecture, education, and religious